Evaluation of the quality of Sorbus fruits belonging to different species - Barabits, E.; Szabó, N.; Sipos, B. Z.; Szenthe, A. (International Journal of Horticultural Science, 2005)
The interest in wild growing fruits was increased considerably by the pharmaceutical industry, the cosmetics as well as by the food industry. (Stefanovits-Bányai et al., 2004). Elderberry (Sambucus nigra L), sand thorn (Hippophae rhamnoides L.), cornet (Cornus mas L.), dog rose (Rosa canina L. bearing hips) and the Sorbus species (Sorhus ssp.) have been well known medicinal and/or ornamental plants since long. Recently, precious substances have been detected in their fruits, which are indispensable in healthy foods. Several species and micro-species of the genus Sorbus are components of the native flora of Hungary, and the fruit of some of them have been consumed traditionally, however, they are preferably considered as ornamentals. The nursery of Alsótekeres (Balatonvilágos) maintained some 16 clones of Sorbus species, which are mainly apomictic "micro species" of. the collection. In 2003, a comprehensive analysis of sorb fruits born on apomictic micro species was initiated in order to find those, which will be suitable to establish plantations. It turned out that considerable differences exist between the fruits of individual taxa, however, it is largely influenced by seasonal effects. According to physical measurements, a scale of mean fruit masses could be established. As for chemical ingredients of the fruits, those are of special interest, which are involved mainly in anti-oxidant activities of the organisms (calcium, potash, phosphorus, copper, magnesium).